IMPLEMENTASI ALAT PERAGA UNTUK MENINGKATKAN MOTIVASI GURU DALAM MENGAJAR DI SD NEGERI 008 PAGARAN TAPAH DARUSSALAM - Zakiah Zakiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to improve teachers' motivation in teaching by using visual aids at SD Negeri 008 PagaranTapah Darussalam. Based on the description on the background, problem identification and problem restriction,the focus of this research is related to the effort to improve the motivation of teaching teachers by using visualaids in SD Negeri 008 Pagaran Tapah Darussalam. The School Action Research is conducted only at SD Negeri008 Pagaran Tapah Darussalam. In one supervision of the researcher himself. The type of this research is theSchool Action Research (PTS) located at SD Negeri 008 Pagaran Tapah Darussalam, which is aimed atteachers. The main reason is from the results of observation and information from teachers, that the teacher'steaching ability is still classified as less. The sample in this study is all teachers in SD Negeri 008 PagaranTapah Darussalam amounted to 11 people. Based on the results of the analysis and discussion as presented inchapter IV, it can be concluded that in the activity aspect of headmaster as facilitator get achievement with score25 or with percentage equal to 63 from all aspect of assessment or equal to 63% all activity achieved. Then onthe second cycle score obtained by 38 or with percentage achievement of 95% of all aspects achieved. Aspects ofteacher activity as a participator in this study in the first cycle of the score obtained from the implementation ofdirection by the principal get a score of 49 or with percentage of achievement of 56%. Then in cycle ii theparticipation rate is 73% higher than cycle i and with the implementation score of 64. teacher motivation aspectduring the execution of the direction from cycle i to cycle ii, teacher motivation in using props tends to rise.where if in cycle i get percentage of achievement of 54% with enough category, then cycle ii get percentageequal to 77% or with category of very good